Pelatihan Troubleshooting Komputer Dasar bagi Siswa Menengah di SMK Pusdikhubad - Ari Sudrajat; Dahlan (Yayasan Pemimpin Inovasi Science, 2026)
Enhancing the competence of Vocational High School students in the field of information technology is a primary priority to address the challenges of Industry 4.0 and the demands of the business and industrial world. Computer Troubleshooting Training is designed to bridge the gap between theoretical mastery in the classroom and students' practical skills in handling various technical issues with computer devices. The primary challenge faced by students is a lack of understanding regarding systematic diagnostic methodologies, which frequently leads to human error during the repair process. This training employs a combination of interactive lectures, demonstrations, and hands-on laboratory sessions. The training modules encompass hardware failure identification and software optimization. The expected outcome of this activity is an increase in students' technical independence and their readiness for job traning. By mastering methodical troubleshooting techniques, students are expected to provide efficient, rapid, and accurate technical solutions within a professional work environment.